Vienna (four views) - Tenhaeff, J.W. (engraver):::Creator:::::::::::: (G. Schubert; Steindr. von E. Bandelow & Co; Leipzig; Germany)
Lithograph with four images of Vienna: the Carls Bridge, the Ferdinands Bridge, the Schwarzenberg Palace, and Michaelsplatz